Empress Wu the Great : Tang dynasty China - Woo, X. L. (Algora Pub., 2008)
Europe and Great Britain have had many sovereign queens in the course of history. In ancient China, there was none of that. Only one Empress ever ruled China in her own name? Empress Wu. Given her startling performance in a world of deadly intrigue and shifting loyalties, Wu is still respected as an effective and clear-sighted ruler.